Hydrometra in Domestic Rabbit- A Case Study - DAS, G K; RISAM, K S (The Indian Journal of Animal Reproduction, 2023)
Present communication records the occurrence of hydrometra in a breeding White Giant rabbit doe from a sub-temperate climate of India.